Sola Gratia as Divine Attribute: Resurrecting the God of the Gospel - Brondos, David A. (Dialog, 2015)
Can we speak of sola gratia as a divine attribute so as to affirm that all that God does is grace? Traditionally, Western Christian theology has answered that question negatively, placing God's justice in opposition with God's grace and presenting a God whose love does not seem to be unconditional. This has been especially evident in the ways in which Scripture, the work of Christ, justification by faith, and the distinction between law and gospel commonly have been interpreted. By rethinking those traditional interpretations on the basis of an understanding of divine grace as unconditional love, we can indeed proclaim a God of sola gratia and a gospel capable of transforming human lives and responding effectively to the crisis of faith we face today.